Water, Energy and Food Nexus: Policy Relevance and Challenges - Orimoloye, Israel R. (Frontiers in Sustainable Food Systems, 2022)
Water resources are a critical environmental benefit for human society and ecosystems to function properly. Water, energy and food are the keys to economic input and a necessary component of economic progress. The adoption of water management policies and techniques that support the sustainable use of resources while promoting economic growth is becoming an important concern, particularly in countries where water and food scarcity are critical or problematic. This study aimed at evaluating Water, Energy and Food Nexus (WEF), and as well as challenges of its implementation. This study looked at the articles that were published on WEF nexus between 2015 and 2021 acquired from the Scopus database, focusing on gaps and implementations. I searched for relevant key terms in the database and the search found hundreds of articles on WEF, of which 28 articles were relevant to the scope of the study and these articles were downloaded as BibTeX file for the analysis and the analysis was done using R programming. A number of insights and implications were identified based on the analyses of the findings of the reviewed research in order to increase the policy relevance and overall implementation of the WEF nexus by public policy and decision-making institutions. To boost uptake of the findings, the study gives an outline of the primary constraints and challenges that restrict the policy relevance of the WEF nexus.